Observation on the effect of nursing intervention based on non-violent communication concept combined with child life medical aid game on school-age children treated with concealed penis surgery - Xiaoye Hu; Xuexia Lian; Le Qin; Shuangli Zheng; Keping Wang; Huishuang Huang (Journal of Men's Health)
Background: This study investigates the clinical effects of an intervention combining the principles of non-violent communication (NVC) and a medical-assisted game on school-age children undergoing concealed penis surgery. Methods: A total of 100 school children who underwent concealed penile surgery were divided into a control group (receiving usual care) and a study group (receiving an NVC-based medical-assisted game intervention). The groups were compared in terms of treatment compliance, children’s medical fear score, wound pain 24 hours post-operation, complications, postoperative recovery and parental satisfaction with nursing care. Results: The treatment compliance rate in the study group was significantly higher than in the control group (p = 0.040 < 0.05). The Children’s Medical Fear Scale (CMFS) scores in the study group were notably lower than those in the control group. The Face, Legs, Activity, Cry and Consolability (FLACC) pain score at 24 hours post-operation was significantly lower in the study group compared to the control group (p < 0.001). The differences were statistically significant. Moreover, no significant differences were observed in operation time and intraoperative blood loss between both groups. However, the study group had a significantly shorter off-bed activity time and hospital stay compared to the control group. Furthermore, the study group exhibited a lower incidence rate of complications (such as hematoma and preputial edema) than the control group. Parental satisfaction with nursing care was significantly higher in the study group (p = 0.037 < 0.05). Conclusions: The intervention combining non-violent communication and medical aid games demonstrates significant clinical benefits for school-age children undergoing concealed penis surgery. It improves treatment compliance, reduces medical fear and postoperative pain, shortens recovery times, lowers complication rates and enhances parental satisfaction with nursing care.